164k views
1 vote
Solve the system of equations step by step also you can use any method to solve this I just need help

X+2y=2 and -x+y=-5

User Aravind NC
by
5.1k points

2 Answers

4 votes

Answer: x = 4

y = -1

Explanation:

Elimination Method:

In an elimination problem, both equations are aranged in the form of an arithmetic problem. One equation must have an offset of either the x or y of the other equation, so as to eliminate the variable for you to solve for the other one. If a variable doesn't have a negative counterpart, multiply the equation by a number so they can offset each other.

Given:

x + 2y = 2

-x + y = -5

Step 1: Solve for x

To solve for x, we need to eliminate the y by creating an equation where the y can eliminate the other equations y.

-2(-x + y = 5) = 2x - 2y = 10

Now that the y's can cancel each other out, we can combine the equations and solve for x.

x + 2y = 2

2x - 2y = 10

3x = 12

x = 12/3

x = 4

This is the value of x

Step 2: Solve for y

The x's can already cancel each other out, so you can just combine the equations and solve for y.

x + 2y = 2

-x + y = -5

3y = -3

y = -1

This is the value of y

Step 3: Verify

To make sure there weren't any mistakes, you need to check by replacing x and y with they're values. x is 4 and y is -1

Substitute: (4) + 2(-1) = 2

Solve: 4 - 2 = 2

Substitute: -(4) + (-1) = -5

Solve: -4 - 1 = -5

The answers are x = 4 and y = -1

User Harsha Vardhini
by
5.3k points
3 votes

Answer:

Solution :

{x,y} = {2/3,2/3}

Explanation:

Solve equation [2] for the variable x

[2] 9x = 6

[2] x = 2/3

// Plug this in for variable x in equation [1]

[1] (2/3) + 2y = 2

[1] 2y = 4/3

[1] 6y = 4

// Solve equation [1] for the variable y

[1] 6y = 4

[1] y = 2/3

// By now we know this much :

x = 2/3

y = 2/3

(I dunno if this is what you meant or not..)

User Emil Salageanu
by
5.3k points
Welcome to QAmmunity.org, where you can ask questions and receive answers from other members of our community.